The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5194/hess-18-3069-2014
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative contribution of climate change and human activities to runoff changes in the Wei River basin, China

Abstract: Abstract. Surface runoff from the Wei River basin, the largest tributary of the Yellow River in China, has dramatically decreased over last 51 years from 1958 to 2008. Climate change and human activities have been identified as the two main reasons for the decrease in runoff. The study period is split into two sub-periods (1958-1989 and 1990-2008) using the Mann-Kendall jump test. This study develops an improved climate elasticity method based on the original climate elasticity method, and conducts a quantita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 36 publications
(45 reference statements)
5
61
1
Order By: Relevance
“…The difference in the observed and simulated streamflows during the changed period was due to the difference in land cover and other human activities. The results indicated that human activities caused significant reductions in streamflow, and these results were consistent with other studies (Chang et al, 2015;Tang et al, 2013;Zhan et al, 2014).…”
Section: Hydrological Model Simulation Resultssupporting
confidence: 82%
“…The difference in the observed and simulated streamflows during the changed period was due to the difference in land cover and other human activities. The results indicated that human activities caused significant reductions in streamflow, and these results were consistent with other studies (Chang et al, 2015;Tang et al, 2013;Zhan et al, 2014).…”
Section: Hydrological Model Simulation Resultssupporting
confidence: 82%
“…In recent years, hydrologists have put great efforts into attribution analysis of changes in runoff [16][17][18][19][20][21][22][23][24][25][26]. Broadly, the attribution analysis methods can be mainly divided into five categories: (1) Paired catchment studies.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been conducted to separate the impact of climate variation and human activities on river discharge [7][8][9]. Using regression techniques Ye et al [10] and Tian et al [11] investigated the effects of climate variability and human activities on the long-term change in runoff of the Lena River Basin and Hutuo River Basin in China; however, a clear conclusion on the magnitude of each of the two factors could not be drawn due to the limitation of the analytical method.…”
Section: Introductionmentioning
confidence: 99%